2013
DOI: 10.1016/j.jacc.2013.02.076
|View full text |Cite
|
Sign up to set email alerts
|

The Transaortic Approach for Transcatheter Aortic Valve Replacement

Abstract: TAVR via the TAO approach is technically feasible, seems to be associated with favorable outcomes, and expands the current alternative options for access sites in patients with inoperable aortic stenosis who are ineligible for TF TAVR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…21 This approach is very familiar to cardiac surgeons and the proximity to the aortic valve under direct aortic access probably provides improved catheter control during implantation. Simultaneous OPCAB with transaortic TAVI has been introduced for patients with comorbidities that require avoiding cardiopulmonary bypass.…”
Section: Resultsmentioning
confidence: 99%
“…21 This approach is very familiar to cardiac surgeons and the proximity to the aortic valve under direct aortic access probably provides improved catheter control during implantation. Simultaneous OPCAB with transaortic TAVI has been introduced for patients with comorbidities that require avoiding cardiopulmonary bypass.…”
Section: Resultsmentioning
confidence: 99%
“…In early reports, Clarke et al [11] found good ease of access and visibility using this method, while Lardizabal et al [15] demonstrated superior mortality rates compared to the TA approach, with comparable complication rates. The short distance from the puncture site to the annulus enabled by the TAo access provides excellent and immediate tactile feedback [16].…”
Section: Discussionmentioning
confidence: 97%
“…In non-randomized studies, the transaortic approach has been shown to result in similar clinical outcomes when compared with the TA approach. 26, 27 Potential advantages of the transaortic approach are avoidance of a thoracotomy and injury to the myocardium and apex, as well as potential for direct visualization of the aorta. In patients with specific high-risk comorbidities such as chronic obstructive pulmonary disease and left ventricular systolic dysfunction, these advantages of the transaortic approach may result in superior HRQoL outcomes.…”
Section: Discussionmentioning
confidence: 99%